Dakwah Berbasis Konseling Islam (Jurnal Bimbingan dan Konseling Islam, 2020)
his paper talks about Islamic counseling-based da'wah. The purpose of Islamic counseling-based da'wah is the integration in the use of the da'wah method with methods in Islamic counseling. The emergence of this merger is because the message of preaching to be conveyed can be received by the public from all walks of life, so that problems in daily life and religious matters can be resolved properly. One way is to use an approach to mad'u very active role in conveying da'wah at the present time. One approach that must be used is through Islamic counseling that has a specific goal that is to help individuals to be able to understand problems, be able to overcome problems that deal with, and help individuals maintain and develop situations and conditions that are good or that remain good to stay good, or become better, so that it will not be a source of problems for themselves and others. The method used in this paper The method used by the author in this research is to use a descriptive analysis method. The authors analyzed the data from written, oral and video sources. The purpose of the source of the article is that the writer analyzes from several research journals related to the title, along with a book that discusses the relationship between da'wah and Islamic counseling. The conclusion of this study is that the emergence of the basic concept of Islamic counseling-based da'wah was addressed to mad'u who have mental problems, confusion and psychiatric problems. The point is to help rediscover himself with the vibrations of his faith in overcoming difficulties encountered, through Islamic counseling methods. Furthermore, the form of preaching based on Islamic counseling is through the use of da'wah methods which are combined with Islamic counseling activities.